Effect of Nasya karma with Ayurveda treatment regimen in the management of Avabhahuka with special reference to frozen shoulder: Case series study - Rajapakse, T.; De Silva, R.H.S.K. (University of Colombo, 2025)
Frozen shoulder (Adhesive Capsulitis) causes pain and reduced mobility, significantly impacting quality of life. Modern treatments often fall short, leading many to seek holistic Ayurvedic care. Ayurveda emphasizes individualized therapies like Panchakarma, Nasya, and herbal remedies. The research is conducted as case series. The subjective parameters were the Shoola (pain) and Stabdha (stiffness). These parameters were modified to objective parameters through Likert Scales ranging from 1 to 4. Five patients aged 59–66 with Avabhahuka (Frozen Shoulder) were selected and treated at two Ayurveda hospitals in Sri Lanka. Patients were selected based on Ayurvedic diagnostic criteria and assessed through pain, stiffness, and range of motion. Treatment included internal and external therapies such as decoctions, herbal formulations, Balakoranda oil, and Nasya karma using Dashamooli bala masha decoction. Outcomes were measured over six weeks through clinical assessments, interviews and subsequently data entry through Likert Scales assigned to each parameter. Ethical approval was obtained, and no compensation was provided. During the data analysis, the subjective data were converted to numerical form using Likert Scales. Then the data were processed using SPSS computer software. The study supports the effectiveness of an Ayurvedic treatment regimen, offering a structured protocol for future clinical application and research. Among the five patients (80% female), aged 59-66, Ayurvedic treatment significantly reduced frozen shoulder pain and stiffness over time. Initial improvements were borderline significant, but long-term results showed meaningful relief (p=0.04771). Patients experienced enhanced mobility and comfort, with one exception due to strenuous physical activity. Nasya Karma with Dashamoola bala masha decoction and Balakoranda oil significantly reduced pain and stiffness in frozen shoulder, especially among middle-aged, Vata-Kapha females. Nasya karma with Dashamoola bala masha and Balakoranda oil shows promise for treating frozen shoulder, warranting further research to validate long-term effectiveness and lifestyle impacts.
Keywords: Avabhahuka; Nasya karma; Balakoranda oil; Dashamooli bala masha decoction